Draft Genome Sequence of a Vibrio parahaemolyticus Strain, KS17.S5-1, with Multiple Antibiotic Resistance Genes, Which Causes Acute Hepatopancreatic Necrosis Disease in Penaeus monodon in the West Coast of Peninsular Malaysia - Devadas, Sridevi; Bhassu, Subha; Soo, Christie Tze Chiew; Iqbal, Suhaina Nashath Mohamed; Yusoff, Fatimah M.; Shariff, Mohamed; Stewart, Frank J. (American Society for Microbiology, 2018)
We report the first draft genome sequence of a Vibrio parahaemolyticus strain (VpAHPND), which causes acute hepatopancreatic necrosis disease (AHPND) in Penaeus monodon. The strain has a pVA1-like plasmid carrying pirAvp and pirBvp genes. Whole-genome comparisons revealed 98% similarity to VpAHPND isolates from Thailand, Mexico, and Vietnam.